El deseo del analista y su configuración topológica (2009)
ABSTRACT: The current article comes from the paper presented by the author during the International Seminar La Topología en la Clínica Psicoanalítica (Topology in Psychoanalytical Clinic) –Medellín, 2008-, in which Lacanian phrase “Desire of the psychoanalyst” is analyzed as an operative concept of psychoanalytical clinic, proposed by Lacan in his teachings, but likely to be articulated to Freud’s thesis about the work of the “clinician” during his psychoanalysis practice.